2021
DOI: 10.3390/coatings11070788
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy towards Superhydrophobic Self-Cleaning and Anti-Corrosion Metallic Surfaces: An Example with Aluminum Alloy

Abstract: Corrosion and contamination of metallic structures can cause loss of their functionality as well as aesthetic values. In this study, we describe a general strategy to prepare superhydrophobic self-cleaning and anti-corrosion surfaces for metallic structures. As a specific example, a superhydrophobic coating (SHC) on aluminum alloy was prepared by a simple etching combined with the decoration of a low-surface-energy material. The optimal SHC has a water contact angle (CA) at ~157.4° and a sliding angle (SA) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Corrosion tests of AMg6 alloy with a hydrophobized surface in the salt fog chamber showed that the coating that we developed withstood 140 h until the first corrosion sites appeared on the substrate, while the natural oxide film provided protection for only 24 h (Figure 3). Thus, the protective ability of the hydrophobic coating formed is comparable to that achieved by applying chromate coatings (130-150 h) or anodic oxide coatings (96-120 h) [29,30,38,49].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Corrosion tests of AMg6 alloy with a hydrophobized surface in the salt fog chamber showed that the coating that we developed withstood 140 h until the first corrosion sites appeared on the substrate, while the natural oxide film provided protection for only 24 h (Figure 3). Thus, the protective ability of the hydrophobic coating formed is comparable to that achieved by applying chromate coatings (130-150 h) or anodic oxide coatings (96-120 h) [29,30,38,49].…”
Section: Resultsmentioning
confidence: 78%
“…However, superhydrophobization requires a surface with multimodal roughness to be formed beforehand to enable the transition from the Wenzel state to the Cassie state, followed by modification with agents that reduce surface energy [3,[24][25][26][27][28]. Anodizing [29,30], chemical vapor deposition [6,8], sol-gel technology [31][32][33], and laser treatment [34,35] are used to impart multimodal roughness onto a surface. Long-chain alkyl and perfluoroalkyl chains are functionalized with a group that allows them to be affixed to the surface and are used as agents with low surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, metals and alloys are the most suitable substrates for chemical etching, especially magnesium alloys or aluminum alloys (Panda, 2021;Peng et al, 2021). By controlling the concentration of etching solution and etching time, the structural characteristics of superhydrophobic surface, such as roughness, can be effectively changed (Wei et al, 2021b;Guo et al, 2021;Krishnan et al, 2021;Zheng et al, 2021) (Figure 2).…”
Section: Chemical Etching Methodsmentioning
confidence: 99%
“…Among these approaches, chemical etching has been highlighted on account of its low cost and high efficiency. Furthermore, several kinds of chemicals, including acid [12][13][14][43][44][45][46][47][48][49]52,53], salt [50,51] and alkali [15,[54][55][56][57][58][59][60][61][62][63][64] solutions, have been widely used as etchants. Among these etchants, alkali solution is preferable because it is more beneficial for the environment.…”
Section: Introductionmentioning
confidence: 99%